Pola Spasial dan Aksesibilitas Penggunaan Pelayanan Kesehatan: Pengobatan Ulang Tuberkulosis - Rohman, Hendra (Universitas Ahmad Dahlan, 2019)
Background: Increased tuberculosis cases and deaths were caused by being untreated, did not understand that tuberculosis bacilli had been infected, coverage rates were low, coverage was high but treatment outcomes were low, and there were new cases due to demographic transitions. The treatment success rate for smear-positive was 86%. In Kulon Progo, based on 73 patients treated in 2013 as many as 59 people were declared cured. The aim of this study was to mapping the distribution pattern of pulmonary tuberculosis patients who re-treat, identify the place of treatment and access to health facilities. Method: A cross-sectional survey using a geographic information system, the sample included 162 pulmonary tuberculosis patient in 2014. The variables were pulmonary tuberculosis patients and distance to health care facilities. Analyzed by descriptive methods. Result: There were 8 cases of recurrent tuberculosis cases, 5 patient was difficult to access. Cases drop out there was 4 patient, 2 patient was difficult to access. The case failed 4 patient, 3 patient was difficult to access. In the rural area was 78%. Results of treatment of tuberculosis relapse in the first quarter, 1 patient was difficult to access, otherwise healed. In the second quarter, 3 patient was difficult to access, 2 patient was declared cured, 1 patient was died, with diabetes mellitus complication. 1 patient was drop out in the first quarter, access was difficult, stated back to follow-up. In the second quarter, 1 patient was easy to access, otherwise recovered. Tuberculosis failed in the second quarter, 1 patient was easy to access, otherwise recovered. Conclusions: The spatial pattern of distribution of pulmonary tuberculosis patients who re-treated was mostly spread in rural areas, patients had difficulty accessing health facilities, patients seeking medical treatment in several health care facilities to move in four different places.